Opioid intake prior to admission is not increased in elderly patients with low-energy fractures: Aa case-control study in a German hospital population - Schwarzer, Andreas; Kaisler, M.; Kipping, K.; Seybold, D.; Rausch, V.; Maier, C.; Vollert, Jan (European journal of pain, 2018)
Background Recent studies revealed an increased prescription rate of opioids for elderly patients suffering bone fractures. To gain further insight, we conducted face-to-face interviews in the present study to compare the opioid intake between patients with low-energy fractures and patients suffering from internal diseases. Methods In this case-control study, 992 patients, aged 60 years and older, were enrolled between March 2014 and February 2015. The interview comprised a fall and medication history, comorbidities, mobility and other risk factors for fractures. Odds ratios (OR) and a multiple logistic regression model were calculated. Results The number of patients with pre-admission opioid intake in the last 12 months was comparable in the fracture (n = 399, 13.3%) and the control group (n = 593, 14.7% OR: 0.89, CI: 0.62-1.29). The number of patients with current opioid intake of short duration (<3 months) was similar in both groups (14% vs. 20%; OR: 0.66, CI: 0.23-1.93). Patients with opioid intake in the fracture group reported more frequently fatigue as an adverse event of opioid medication (58% vs. 30%; OR: 3.32, CI: 1.48-7.45). Patients with opioid intake showed more severe comorbidities and significantly decreased mobility compared to those without opioids. Conclusion Elderly patients internalized due to low-energy fractures did not take opioids more frequently than patients with internal admission, for both short (<3 months) and longer duration intake. Patients with opioid intake were generally in poorer physical condition. The risk of fracture might increase in patients suffering from fatigue as a side effect of opioid medication. Significance This study is based on face-to-face interviews with patients, including details about side effects and fracture history, providing a more pronounced picture of the relation of opioid intake and risk of fracture.
Gesehen am 04.09.2019